Pengaruh Demografi Terhadap Foreign Direct Investmen di Negara Asia Selatan - H. Masri, Zainal Arifin; Alam, Bambang Perkasa; Barkah, Januar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This research aims to explore the influence of demographic factors on foreign direct investment (FDI) in India, Pakistan, and Bangladesh. Through related data and literature, we identified that demographic factors such as the low-income population, children suffering from stunting, and low-educated residents can significantly impact FDI flows. This study provides valuable insights for policymakers and investors to understand the dynamics of investment in India, Pakistan, and Bangladesh. The research uses a quantitative method. Data on FDI, the low-income population, children suffering from stunting, and low-educated residents for India, Pakistan, and Bangladesh were obtained from the World Bank. The period covered is from 2015 to 2021. The results show that simultaneously, the low-income population, children suffering from stunting, and low-educated residents significantly affect economic growth, as indicated by a probability (F-statistic) of 0.000000, which is less than 0.05. Individually, the low-income population significantly influences economic growth, as shown by a probability of 0.0000, which is less than 0.05. However, children under five suffering from stunting do not affect economic growth, as indicated by a probability of 0.6023, which is greater than 0.05. Similarly, low-educated residents do not affect economic growth, as indicated by a probability of 0.0646, which is greater than 0.05.